VHF radar observations of turbulent structures in the polar mesopause region - P. Czechowsky; R. Rüster (Annales Geophysicae, 1997)
The mobile SOUSY VHF Radar was operated in the summer of 1987 during the MAC/SINE campaign in northern Norway to study the polar mesosphere summer echoes (PMSE). Measurements of the spectral width indicate that two types of structures occur. In general mesospheric layers are bifurcated exhibiting a narrow spectral width and a well-defined aspect sensitivity. However, for about 10% of the observation time cells of enhanced turbulence characterized by extremely broad spectral widths appear predominantly in the upper sublayer above 86 km. Identification and separation of beam and shear broadening allows a determination of the turbulence-induced component of the spectral width. This case study reveals that during several events these cloud-like structures of enhanced turbulence move with an apparent velocity of several tens of meters per second which is almost identical with the phase trace velocity of simultaneously observed waves. Since, at that time, the Richardson number was less than a quarter, it was concluded that these turbulent cells were generated by a Kelvin-Helmholtz mechanism. The horizontal extent of these structures was calculated to be less than 40 km. A general relation between spectral width and echo power was not detected. The turbulent component of the spectral width was used to calculate typical values of the energy dissipation rate at times where narrow spectral width dominates and during periods of enhanced turbulence. In addition, the outer scale of the inertial subrange (buoyancy scale) was estimated. For the first time the occurrence and motion of this type of structures of enhanced spectral width is analyzed and discussed in detail.